PERSEPSI PENGURUS LINGKUNGAN TENTANG LINGKUNGAN DAN KEDEWASAAN IMAN UMAT PAROKI SANTO CORNELIUS MADIUN DALAM PERSPEKTIF ARDAS KEUSKUPAN SURABAYA - Ginting, Alvaro Kristoforus; Wilhelmus, Ola Rongan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
The Church is a dynamic institution because of human and social life continues to be changing from time to time. Based on the social and human changes, the Second Vatican Council called for an Aggiornamento or renewal in order to make the Church to be able to provide relevant and contextual services for all of the faithful people. This Aggiornamento urges the Church to renew itself and be more open to the present social and human condition in an ever-changing society. Based on the background of the research problem, the researcher then formulated this research problem as the following: what is the perception of the basic Christian Community administrators about the typical characteristics of the maturity in faith? The aim of the research is to analyze the perceptions of the Basic Christian Community administrators regarding those characteristics of the maturity in faith. The research applied a quantitative method. The research data analysis used a descriptive and inferential statistics. Data collection for the research used a questionnaire technique. The respondents of the study were Basic Christian Community administrators, namely: Basic Christian Community chairman, Basic Christian Community deputy, secretary, treasurer and other Basic Christian Community administrators in St. Cornelius Parish, Madiun city. The results of the study showed that the majority of respondents viewed Basic Christian Community as the most visible part of the Church's presence as a fellowship of Christ's disciples in society. Respondents believed that the maturity of a person's faith was revealed through such guidance and inclusion of the Holy Spirit in everyday life.